Analysis of User Reviews of Online Learning Applications - Noerhartati, Endang; Dita Handani, Narariya (Universitas Islam Sultan Agung, 2024)
This study aims to analyze user reviews of Muslim students of the Ruangguru online learning application in Indonesia using word frequency and co-occurrence analysis methods from March 2020 to February 2023. By applying a qualitative approach to extensive review data, this study identifies the factors that influence satisfaction and user preferences in the online learning process. The results show that usability, content quality, interactivity, and technical support are important aspects that contribute to the user learning experience of Muslim students. However, there are also challenges experienced by users, such as technical problems and the need for further personalization. These findings provide valuable insights for online learning application developers to improve the quality of their products and support educational needs in Indonesia. This research also suggests conducting a quantitative study to dig deeper into users' subjective experiences.